2020
DOI: 10.1002/app.48812
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organoclays on the phase morphology and the compatibilization efficiency of immiscible poly(ethylene terephthalate)/poly(ε‐caprolactone) blends

Abstract: Adding nanofillers Cloisite 30B (C30B) and Cloisite 15A (C15A) to poly(ethylene terephthalate) (PET)/poly(ε‐caprolactone) (PCL) (70/30, wt/wt) blends via melt blending can improve their phase morphology and change their interface properties. The effects of the different selective localization of clay on the structure and the morphologies are studied and evaluated by theoretical and experimental methods. It is found that C30B is selectively localized in PET and at the PET‐PCL interface, whereas C15A is mainly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Figure d shows the mechanical property intensification advantage of the VPIM technique. In comparison with the approaches of adding external components, , the tensile strength of PET has been enhanced but the larger enhancement in elongation at break (ductility) under the VPIM technique, indicating self-toughness and self-reinforcing of PET are achieved simultaneously. As shown in Figure d, the additional components such as PCL/C30B, PSG, CATAS, PLA, clay, PLA/SA-GMA can enhance tensile strength by a comparable magnitude, while these PET blends show a sharp reduction in elongation at break.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure d shows the mechanical property intensification advantage of the VPIM technique. In comparison with the approaches of adding external components, , the tensile strength of PET has been enhanced but the larger enhancement in elongation at break (ductility) under the VPIM technique, indicating self-toughness and self-reinforcing of PET are achieved simultaneously. As shown in Figure d, the additional components such as PCL/C30B, PSG, CATAS, PLA, clay, PLA/SA-GMA can enhance tensile strength by a comparable magnitude, while these PET blends show a sharp reduction in elongation at break.…”
Section: Resultsmentioning
confidence: 97%
“…Numerous researches have been performed on improving mechanical properties by promoting crystallization. Huang et al employed nucleating agents to promote the crystallization of PET to achieve the enhancement of tensile strength . Zhang used PMA-AA ionomer to provide more nucleation sites to improve the crystallization properties of PET, which achieved the intensification of tensile strength .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the tensile strength and flexibility of PCL films with nanoclay additives gives the result that the packages can be mechanically more resistant to external stresses (Sogut & Seydim, 2018). The mechanical properties are affected by the method of film formation, exfoliation degree of nanoclays in a polymer matrix, three‐dimensional network of nanoclays, and crystallization degree of polymer simultaneously (Elghaoui et al, 2020; Saaoui et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The polymer penetration into the clay galleries may cause the delaminated platelets (individual layers) or intercalated ones in the stacks with larger spacing among the platelets. [11][12][13][14][15] It was reported that the ion-exchange procedure by alkyl ammonium ions can enhance the hydrophobicity of clay surface and expand the clay packs, which enable the diffusion of polymer molecules into the clay channels. 16 Generally, the nanometer size of clay in the nanocomposites causes outstanding powered, physical, thermal, and barrier features, since the nano-platelets maximize the interfacial region with the polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoclay is a respectable applicant for the construction of organic–inorganic nanocomposites, since it can be destroyed to nano‐platelets 1–10 . The polymer penetration into the clay galleries may cause the delaminated platelets (individual layers) or intercalated ones in the stacks with larger spacing among the platelets 11–15 . It was reported that the ion‐exchange procedure by alkyl ammonium ions can enhance the hydrophobicity of clay surface and expand the clay packs, which enable the diffusion of polymer molecules into the clay channels 16 .…”
Section: Introductionmentioning
confidence: 99%